Prenatal Exposure to Methamphetamine: Up-Regulation of Brain Receptor Genes - Zoubková, Hana; Tomášková, Anežka; Nohejlová, Kateryna; Černá, Marie; Šlamberová, Romana (Frontiers in Neuroscience, 2019)
Methamphetamine (METH) is a widespread illicit drug. If it is taken by pregnant women, passes through the placenta and just as it affects the mother, it can impair the development of the offspring. The aim of our study was to identify candidates to investigate for changes in the gene expression in the specific regions of the brain associated with METH addiction in rats. We examined the various areas of the central nervous system (striatum, hippocampus, prefrontal cortex) for signs of impairment in postnatal day 80 in experimental rats, whose mothers had been administered METH (5mg/kg/day) during the entire gestation period. Changes in the gene expression were determined by two methods, microarray and real-time PCR. Results of two microarray trials were evaluated by LIMMA analysis. The first microarray trial detected either up-regulated or down-regulated expression of 2189 genes in the striatum; the second microarray trial detected either up-regulated or down-regulated expression of 1344 genes in the hippocampus of prenatally METH exposed rats. We examined the expressions of 10 genes using the real-time PCR method. Differences in gene expression were counted by the Mann–Whitney U test. Significant changes were observed in the cocaine- and amphetamine-regulated transcript prepropeptide, tachykinin receptor 3, dopamine receptor D3 genes expression in the striatum regions, in the glucocorticoid nuclear receptor Nr3c1 gene expression in the prefrontal cortex and in the carboxylesterase 2 gene expression in the hippocampus prenatally METH exposed rats. The microarray method also detected upregulated expression of trace amine-associated receptor 7h gene in the hippocampus of prenatally METH exposed rats. We have identified susceptible genes; candidates for the study of an impairment related to methamphetamine addiction in the specific regions of the brain.